Melanoma-associated antigen A11 reduces erlotinib and afatinib efficacy in head and neck cancer. Issue 3 (March 2018) - Hartmann, Stefan; Zwick, Leonie; Maurus, Katja; Fuchs, Andreas R.; Brands, Roman C.; Seher, Axel; Kübler, Alexander C.; Müller-Richter, Urs D.A.
Abstract: Melanoma-associated antigen A (MAGE-A) proteins are members of the cancer/testis antigens (CTA), and the expression of these proteins is almost exclusively limited to malignant cells, making them an attractive treatment target. MAGE-A expression is correlated with poor overall survival in several cancers, including head and neck squamous cell carcinoma (HNSCC). Among others, MAGE-A11 was found to be associated with resistance to different antineoplastic and targeted compounds, such as epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). We searched The Cancer Genome Atlas (TCGA) database with a focus on MAGE-A and found that MAGE-A overexpression is a common event in HNSCC (27.5%). Furthermore, MAGE-A overexpression was correlated with significantly reduced overall survival (35.45 months vs. 64.78 months, P = 0.0173). In particular, MAGE-A11 overexpression was found in 9% of specimens. We then examined MAGE-A11 expression, the efficacy of EGFR and the EGFR mutational status and the effects of the pan-HER (human EGFR) TKIs erlotinib and afatinib in HNSCC cell lines. Next, we used a model of stable MAGE-A11 overexpression to demonstrate that MAGE-A11 impaired the efficacy of erlotinib and afatinib. In summary, our study provides evidence that MAGE-A11 contributes to erlotinib and afatinib resistance in head and neck cancer cell lines.